La crise écologique exige une révolution de l’économie des services - Jean Gadrey (Développement Durable et Territoires)
In order to build ecological economics of services, we need first to investigate the question of the environmental pressure that services exert and how to measure it. It appears that the alleged immateriality of services in largely a myth. Consequently, the trend towards increased service-sector employment could possibly be affected or even reversed, as far as environmental externalities are internalized and agriculture and manufacturing reoriented on a nonproductiviste way. But such an analysis ought to be carried out at a more detailed industry level than the traditional division in three sectors.